The Validity of the ODARA in Australian Intimate Partner Violence Cases Without Prior Assault/Credible Threat or Cohabitation - Mcewan, Troy E. (Criminal justice and behavior, 2023)
This study investigated whether the Ontario Domestic Assault Risk Assessment (ODARA) is effective in the assessment of risk in male intimate partner violence (IPV) cases that do not meet the inclusion criteria used in the ODARA’s development sample (presence of prior assault or threat by perpetrator and previous cohabitation with the victim). Australian police scored the ODARA in 275 IPV cases without one or both of these characteristics, with results contrasted to performance in 200 cases meeting both inclusion criteria. The ODARA demonstrated poor discriminant effect over time for both assault and abuse recurrence in the former group (concordance index [c-index] = 0.56 and c-index = 0.57, respectively), but performed well in the latter group (c-index = 0.69 and c-index = 0.69). Although subject to some significant methodological limitations and requiring replication, these findings suggest the ODARA may not provide accurate risk-based classification if applied to cases missing the inclusion criteria.